2016
DOI: 10.3926/jiem.2082
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the carbon footprint of material handling equipment: Comparison of electric and LPG forklifts

Abstract: Abstract:Purpose: The aim of this study is to identify the best Material Handling Equipment (MHE) to minimize the carbon footprint of inbound logistic activities, based on the type of the warehouse (layout, facilities and order-picking strategy) as well as the weight of the loads to be handled.Design/methodology/approach: A model to select the best environmental MHE for inbound logistic activities has been developed. Environmental performance of the MHE has been evaluated in terms of carbon Footprint (CF). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…In recent times, the increase of energy efficiency is a pivotal goal for energy policy makers that aim at promoting a conscious, cost-effective, and sustainable energy use in management of resources and infrastructures [1], transportation and logistics [2], the production and industrial sector [3], and all activities related to human life [4]. A significant part of energy consumption concerns the energy demand of buildings that in Europe amounts to 40% of the total and is mainly due to the so-called Heating, Ventilation and Air Conditioning (HVAC) systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the increase of energy efficiency is a pivotal goal for energy policy makers that aim at promoting a conscious, cost-effective, and sustainable energy use in management of resources and infrastructures [1], transportation and logistics [2], the production and industrial sector [3], and all activities related to human life [4]. A significant part of energy consumption concerns the energy demand of buildings that in Europe amounts to 40% of the total and is mainly due to the so-called Heating, Ventilation and Air Conditioning (HVAC) systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the human fatigue, evaluated on the base of an ergonomic approach, are investigated in order picking activities in logistic warehouses. Preliminary findings of the experimental study shown that in most cases there is a reversed u-shaped interrelation between physical fatigue and cognitive performance, whereas the ergonomic of the workplace appears to have a quite variable influence on fatigue effects [16,17]. A detailed review of the most common observational methods is proposed by Roman-Liu, where OWAS, revised NIOSH, OCRA, REBA, LUBA, and EAWS are compared [18].…”
Section: Introductionmentioning
confidence: 99%
“…The design of those collecting centers depends on several factors related to logistic constrains, food cold chain performance, as well as supply chain network. In all cases, the sustainability is considered as the central point of the issue [6]. According to Seuring and Muller, a supply chain network can be defined sustainable when information, capital flows, and cooperation among companies along the supply chain allow to minimizing the impact under economic, environmental and social perspective, keeping under consideration the stakeholder' interests [7].…”
Section: Introductionmentioning
confidence: 99%
“…Along with these policies addressed to minimize the industrial environmental impacts, many companies have realized that the sustainable use of resources may also be associated with financial savings. In this regard, the Carbon Footprint (CF) and Management Costs (MCs) are relevant for measuring the goodness of the picked resources [6,16].…”
Section: Introductionmentioning
confidence: 99%